Kongruensi Unsur Idempoten Ortogonal dalam Aljabar Insidensi Finitary - Carnia, Ema; Wahyuni, Sri; Irawati, Irawati; Setiadji, Setiadji (Jurnal Natur Indonesia, 2011)
Let X be a partially ordered set, R is a commutative ring with identity and FININC (X, R) denote finitary incidencealgebra of poset X over R. In this paper it will be seen congruence of two elements that are idempotent orthogonalin FININC (X, R) relative to the modulo Radical Jacobson of algebra. Review of this topic would be useful to examineisomorphism problems of the finitary incidence Algebra.